DETECTION OF DIATOMS IN NON-DROWNING CASES - A POST-MORTEM STUDY (Journal of Forensic Medicine & Toxicology, 2017)
Diatom test was thought to be gold standard in diagnosis and confirmation of drowning related deaths. Besides determination of cause of death, it also helps to deduce the site of drowning. However, since detection of diatoms in the lung fields of non-drowned deaths in workers of kieshelgur industries by Otto H in the year 1961, many workers claimed that diatoms were also found in lung as well as other peripheral organs in non-drowned individuals, raising serious doubt about the reliability and utility of diatom test. Many of strong supporters of diatom test still rely upon it and attributed presence of diatoms in non-drowned deaths to post-mortem contaminations. Amid controversy surrounding the diatom test, the present study conducted over 750 different tissues from 150 non-drowned deaths using Nitric acid digestion method, diatoms could be detected in 27(18%) cases and 49 (6.53%) different tissues. Small sizes pinnate shaped diatoms were mostly found in liver, kidney, brain and bone marrow tissues where as both small and large sizes diatoms were found in lung tissues.
Keywords: Diatom; Diatom test; Non-drowned deaths; Diagnosis; Reliability